Advances and Prospects in Stem Cells for Cartilage Regeneration - Mingjie Wang; Zhiguo Yuan; Ning Ma; Chunxiang Hao; Weimin Guo; Gengyi Zou; Yu Zhang; Mingxue Chen; Shuang Gao; Jiang Peng; Aiyuan Wang; Yu Wang; et al. (Stem Cells International)
The histological features of cartilage call attention to the fact that cartilage has a little capacity to repair itself owing to the lack of a blood supply, nerves, or lymphangion. Stem cells have emerged as a promising option in the field of cartilage tissue engineering and regenerative medicine and could lead to cartilage repair. Much research has examined cartilage regeneration utilizing stem cells. However, both the potential and the limitations of this procedure remain controversial. This review presents a summary of emerging trends with regard to using stem cells in cartilage tissue engineering and regenerative medicine. In particular, it focuses on the characterization of cartilage stem cells, the chondrogenic differentiation of stem cells, and the various strategies and approaches involving stem cells that have been used in cartilage repair and clinical studies. Based on the research into chondrocyte and stem cell technologies, this review discusses the damage and repair of cartilage and the clinical application of stem cells, with a view to increasing our systematic understanding of the application of stem cells in cartilage regeneration; additionally, several advanced strategies for cartilage repair are discussed.